Improved three-phase power-flow methods using sequence components - Abdel-Akher , Mamdouh (Institute of Electrical and Electronics Engineers, 2005)
The paper presents the formulation and the solution of the three-phase power-flow problem using sequence components. An improved sequence component transformer model and a decoupled sequence line model were used. As a result, the three sequence admittance matrices are decoupled with three-phase power system features in sequence components. The sequence power-flow algorithm has been formulated such that the single-phase power-flow programs can be called as routines for solving the positive sequence network. The results for the proposed sequence power-flow methods are identical to those obtained from three-phase power-flow programs developed in phase components. The computational efficiency and convergence of the proposed sequence three-phase power-flow methods show that they are as fast and as robust as conventional the Newton-Raphson method.